2019
DOI: 10.3390/ma13010130
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role of Ascorbic Acid in Anti-Inflammatory Pathway and ROS Generation in HEMA Treated Dental Pulp Stem Cells

Abstract: Resin (co)monomers issued from restorative dental materials are able to distribute in the dental pulp or the gingiva, to get to the saliva and to the flowing blood. Many authors have recently shown that methacrylate-based resins, in particular 2-hydroxyethylmethacrylate (HEMA), are responsible of inflammatory and autophagic processes in human dental pulp stem cells (hDPSCs) while ascorbic acid (AS), an antioxidant molecule, can assume a protective role in cell homeostasis. The purpose of the current work was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 77 publications
3
29
0
Order By: Relevance
“…In agreement with previous studies [ 53 , 54 , 55 ], the data obtained in the present work demonstrated that treatment with AA showed a reduction in the expression levels of the NLP3 inflammasome that led to a reduction in the production of IL-1β through the TLR4/MyD88/NFκB signaling pathway in the hGMSCs and e-hGMSCs. Moreover, our findings evidenced a protective role played by AA through the modulation of TLR4/MyD88/NFκB/NLRP3/Caspase-1/IL-1β, reestablishing the microenvironment before LPS-G stimulation.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies [ 53 , 54 , 55 ], the data obtained in the present work demonstrated that treatment with AA showed a reduction in the expression levels of the NLP3 inflammasome that led to a reduction in the production of IL-1β through the TLR4/MyD88/NFκB signaling pathway in the hGMSCs and e-hGMSCs. Moreover, our findings evidenced a protective role played by AA through the modulation of TLR4/MyD88/NFκB/NLRP3/Caspase-1/IL-1β, reestablishing the microenvironment before LPS-G stimulation.…”
Section: Discussionsupporting
confidence: 93%
“…Ascorbic acid also has potent anti-inflammatory properties (Diomede et al, 2020), therefore; positively influencing host-defence mechanism towards tissues repair during infection (Goldschmidt, 1991). Its antiscorbutic properties play a pivotal role in the synthesis of collagen through its ability to act as an electron-donor maintaining the ferrous in collagen hydroxylases in an active state (Du et al, 2012).…”
Section: Ascorbic Acidmentioning
confidence: 99%
“…gingivalis , G), that afflicts a large number of people [ 16 , 17 ]. Ascorbic acid (AA), known as vitamin C or ascorbate, consumed as a dietary supplement is a water-soluble vitamin that helps many enzyme activities [ 18 ]. AA is deeply involved in the reduction of reactive oxygen species (ROS) and showed a key role as an antisenescence agent [ 19 ].…”
Section: Introductionmentioning
confidence: 99%